Pembelajaran Tahfidz Al-Qur'an Pada anak Penyandang Disabilitas - Fauziyah, Nisa'ul; Rozi, Syaikhu; Saifuddin (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to examine the implementation of tahfidz Al-Qur'an learning for students with special needs at SLB Negeri Seduri Mojokerto by focusing on three main aspects, namely the characteristics of the students who participate in the program, the learning objectives to be achieved, and the learning strategies used by teachers in the implementation process. This study uses a qualitative approach with a single case study design. Data were obtained through in-depth interviews with school principals, Islamic religious education teachers, and special assistant teachers, direct observation of learning activities, and documentation review. Data analysis was carried out by the stages of data reduction, data presentation, and conclusion drawn, while the validity of the data was tested through the source triangulation technique. The results of the study showed that the students involved in the tahfidz program were students with visual impairment, physical disability, and mild intellectual, with the dominance of visually impaired students because their learning characteristics were more in accordance with auditory and tactile methods. The purpose of tahfidz learning is not only directed at the achievement of memorization, but also at strengthening faith, forming morals, and internalizing spiritual values in daily life. The learning strategies applied include daily routine deposits, talaqqi and tikrar methods, the use of audio murottal, the use of Braille Qur'an, and digital media support such as Qur'an pens. Evaluations are carried out flexibly taking into account the individual abilities of the students. The conclusion of this study emphasizes that the success of the tahfidz program is influenced by the suitability of the strategy with the characteristics of the students, the clarity of learning objectives, and the synergistic support of teachers, parents, and the school environment as the main supporting factors.